Substrate-Assisted Visualization of Surfactant Micelles via Transmission Electron Microscopy - Zhang, Zekun; Li, Kaitao; Tian, Rui; Lu, Chao (Frontiers in Chemistry, 2019)
The visualization of the micellar morphological evolution for surfactant has drawn much attention due to its self-assemble ability to fold into various structures. However, the direct observation of the soft materials with low atomic number has been hampered because of the poor scattering contrast and complex staining process by the traditional transmission electron microscopy (TEM) techniques. Herein, we reported a novel strategy to the visualization of surfactant micelles with the assistance of layered double hydroxides (LDHs) via TEM. Owing to the uniformly distributed metal ions and positive charges in the LDHs, the surfactant at the micelle-water interface reacted with LDHs to form a stabilized architecture through electrostatic and hydrogen-bond interactions. The morphologies of the surfactant can be clearly observed through the surfactant-LDHs architectures, exhibiting high contrast by TEM techniques. Significantly, the micellar evolutions involving the spherical, rodlike and wormlike shapes were successfully distinguished. Our results may provide great possibilities and inspirations for the visualization for morphology of soft matters.